Representasi Identitas Agama dalam Pilkada sebagai Media Resolusi Konflik Etnoreligius di Mamasa - Mahyuddin Mahyuddin; Muhammad Zaldy Febry (Palita: Journal of Social Religion Research, 2023)
Social conflict in Mamasa was a crucial issue. The conflict which initially had a political dimension has led to ethnic and religious conflicts. Various efforts to rebuild the social integration of the community continue to be carried out. This study aims to examine the role of religious identity representation as media of conflict resolution in building social reintegration. The author analyzes the electoral arena in Mamasa which always provides space for religious representation in contesting. The research used an ethnographic approach to explain this phenomenon. Data collection techniques were carried out by observation, interviews and documentation. This study found that religious representation in the regional head election has a significant role in the process of social reintegration of the community in Mamasa district, West Sulawesi. In the process, the community does not rely on extreme identity politics (ethnic and religious) but rather builds moderate political awareness. These political choices contribute to the development of social integration in society.